Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Melalui Profitabilitas Sebagai Variabel Intervening (Jurnal Paradigma Akuntansi, 2022)
The study aims to determine the effect of financial performance through profitabilityon value of banking on BEI 2015-2019. The samples obtained 26 companies using purposivesampling. Path analysis with SPSS and sobel test as data analysis. The F test model 1 significant,t test: non-performing loan, operating efficiency ratio has a significant negative effect,meanwhile loan to deposit ratio has an insignificant effect on profitability. The F test model 2significant, t test: loan to deposit ratio, operating efficiency ratio has a significant negative effect,meanwhile non-performing loan, profitability has an insignificant effect on value of banking.The t test (Intervening) indicates non-performing loan, loan to deposit ratio, operating efficiencyratio through profitability insignificantly on value of banking. The implication of this study isregards to performance more than profitability.